(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2023)
Character creation is probably the most important mode of paintings by artists and the most avowed practice and recognized ontology of the anthropomorphic predominance in art anywhere in the world. This phenomenon can be productively discussed in the context of the art traditions. Discussions about character creation in paintings sound tautological but such practices and styles of the painters of any culture and tradition can be a heuristically productive and viable topic. Though the subject is very broad, we can find some interesting creative developments by studying the traditions of art in any society and culture. The subject can encompass broader geo-cultural spheres like Eastern and Western art, and more specific topics like character creation in Nepali paintings—a study of tradition and development. In this article I will focus on this very aspect of Nepali paintings, not sculpture, by bringing my own experience of appreciating, visualizing and theorizing the human motif primarily body and secondarily features related to that. Though I briefly allude to some historical developments I will focus more on the later developments especially from the time when pedagogy in art started in earnest from the early decades of the twentieth century. The basis of the survey is my own understanding of the subject. I have evoked briefly my own perception of the subject as written in my art reviews and articles.